Histomorphometric analysis of the pectoralis major muscle of elderly and non-elderly autopsied patients with and without AIDS (Research, Society and Development, 2021)
Introduction: The Acquired Immunodeficiency Syndrome (AIDS), an infectious disease, where the main characteristic is the suppression of immunity by T CD4 lymphocytes. Objective: To analyze the percentage of myocytes and collagen fiber density from autopsied fragments of skeletal striated musculature from elderly and non-elderly patients with and without AIDS. Methodology: Retrospective, observational, analytical and quantitative study carried out from 78 divided into four groups, elderly and non-elderly with and without AIDS, aged between 44 and 63 years. Results: For histomorphometric analysis of the percentage of myocytes using Hematoxylin and eosin methods and for collagen fibers and Picrosirius under polarized light, both were performed under ordinary light microscopy. Results: There was a statistically defined decrease in nuclei in the non-elderly groups with and without AIDS and elderly with AIDS compared to the elderly groups without AIDS (p˂0,001). Collagen fibers in the non-elderly and non-deaf AIDS groups were higher when compared to the elderly groups with and without AIDS (p=0,001). The correlation between nucleus and cytoplasm was negative and low in the four groups (p